Effects of spirulina supplementation on body composition in adults: a GRADE-assessed and dose–response meta-analysis of RCTs - Mohammadyasin Lak; Mehdi Karimi; Camellia Akhgarjand; Shirin Ghotboddin Mohammadi; Pedram Pam; Damoon Ashtary-Larky; Samira Pirzad; Mohammadreza Amirkhan-Dehkordi; Mohammad Amin Shahrbaf; Menno Henselmans; Omid Asbaghi (Nutrition & Metabolism)
Abstract Background and Aim Weight management remains a global health concern, with increasing interest in nutritional interventions to support healthy body composition. In recent years, the potential role of supplements like Spirulina has gained considerable attention as a possible intervention. This meta-analysis aims to evaluate the effectiveness of Spirulina supplementation on body composition in adults. Methods A comprehensive search strategy was conducted across online databases to find relevant RCTs from inception until December 2024. The primary endpoints were changes in anthropometric indices. Meta-analysis and meta-regression were performed using STATA software, and sensitivity, subgroup, and publication bias analyses were also conducted. Results The pooled analysis of 17 RCTs indicated that Spirulina supplementation significantly reduced body weight (BW) (WMD: -1.07 kg; p = 0.004), body mass index (BMI) (WMD: -0.40; p = 0.025), body fat percentage (BFP) (WMD: -0.84%; p = 0.002), but had no significant effects on waist circumference (WC) (WMD: -0.46 cm; p = 0.280). Based on Egger’s regression test, there is no publication bias for BW (p = 0.097), BMI (p = 0.382), BFP (p = 0.945), and WC (p = 0.488). A significant dose–response effect on BMI and intervention dose (Coefficient: -0.17, P = 0.007) and duration (Coefficient: 0.13, p = 0.042). Conclusion Spirulina supplementation effectively reduces BW, BMI, and BFP, with stronger effects at higher doses and longer durations, especially in obese or older individuals. While no significant change in WC was observed overall, subgroup analyses suggest potential benefits for specific populations, emphasizing the importance of personalized supplementation strategies.